SM-ND AGE OF DUNITE-CLINOPYROXENITE-TYLAITE ASSOCIATION OF THE KYTLYM MASSIF, THE PLATINUM BELT OF THE URALS - Popov V.S.; Belyatsky B.V. (My University, 2006)
In this communication, we present new data on the Sm–Nd age of clinopyroxene-bearing dunite, wehrlite, olivine clinopyroxenite, kosvite (including an apatite variety), and tylaite (including a pseudoleucite variety) that compose the Kosvinsky and Konzhakovsky blocks in the Kytlym Massif (Fig. 1). The results obtained substantially change the traditional view on the timing and geodynamic setting of ultramafic and mafic rocks in the Platinum Belt of the Urals.
Keywords: Kytlym massif; Urals